Seeking passage : post-structuralism, pedagogy, ethics - Martusewicz, Rebecca A. (New York : Teachers College Press, 2001)
In this collection of essays, Rebecca Martusewicz positions a philosophy of education that relies on what transpires between teachers and learners in various contexts. She thoughtfully analyzes how, in the relationship between teachers and learners, all kinds of ideas, beliefs, interpretations, and meanings are generated as a result of potent generative forces that depend, as she demonstrates using post-structuralist theories, on difference as their fuel. Ultimately she argues that to become educated requires an attention to the welfare of self and others and a willingness to confront and shift one's own habits, practices, and beliefs for that purpose.
Includes bibliographical references and index.
Keywords: Education -- Philosophy; Postmodernism and education; Poststructuralism